Weight Status and High Blood Pressure Among Low-Income African American Men - Marino A. Bruce PhD (American Journal of Men's Health, 2011)
Obesity is a biological risk factor or comorbidity that has not received much attention from scientists studying hypertension among African American men. The purpose of this study was to examine the relationship between weight status and high blood pressure among African American men with few economic resources. The authors used surveillance data collected from low-income adults attending community- and faith-based primary care clinics in West Tennessee to estimate pooled and group-specific regression models of high blood pressure. The results from group-specific logistic regression models indicate that the factors associated with hypertension varied considerably by weight status. This study provides a glimpse into the complex relationship between weight status and high blood pressure status among African American men. Additional research is needed to identify mechanisms through which excess weight affects the development and progression of high blood pressure.